Women's Education: An Important Tool for Birth Reduction? A GMM - Poisson Regression Model Approach - Yedan, Ali (Advances in Social Sciences Research Journal, 2020)
Burkina Faso is a country with a shallow level of woman’s education. However, it is one of the most fertile countries. This paper analyzes whether the education of women reduces the number of births and the Total Fertility Rate in Burkina Faso. It also predicts the average number of births per woman and the Total Fertility Rate if women were better educated. Using data from the Demographic and Health Surveys, I model the two-stage Generalized Method of Moments (GMM) with the Heckman model and Poisson regression. The results show that the high fertility in Burkina Faso is mainly due to the low level of the woman’s education. The post-primary education increases the age at first birth. The number of births per woman would be decreased in the quarter and the Total Fertility Rate would pass from 5.4 to 3.6 if all women had at least completed the primary school. If all women had at least an incomplete secondary school, the number of births per woman would halve and the Total Fertility Rate would become 2.0. The government would do better to improve the education system allowing a good education for all, especially for women if it intends to reduce fertility.